Analisis Pengaruh Budaya Kaizen Terhadap Kinerja Karyawan Dengan Reward Sebagai Variabel Moderasi Dalam Rangka Penguatan Daya Saing Bisnis - Erix Irvan Pamungkas; Rosaly Franksiska (Jurnal Manajemen Dayasaing, 2018)
Every company has its own organizational culture, in which the organizational culture will affect the employee performance and also company performance. Kaizen culture originated from Japan is a culture of continuous improvement with low cost and the impact can be felt in the future. If the Kaizen culture combined with reward will also be able to improve the employee performance. The purpose of this research is to analyze the influence of Kaizen culture to employee performance with reward as a moderating variable. This a quantitative exploratory research using Moderated Regression Analysis (MRA). The data collection method is using questionnaire, with sample of 93 respondents of warehouse department of PT SM Karangjati, Semarang. The result of this study indicated that Kaizen culture influence employee performance and reward can moderate or strengthen the impact of Kaizen culture on employee performance.